Diana Mishkova, Beyond Balkanism: The Scholarly Politics of Region Making - Stamatopoulos, Dimitris (Historein, 2021)
Review of Diana Mishkova. Beyond Balkanism: The Scholarly Politics of Region Making. London: Routledge, 2018. 282 pp.